Collegiate Connections: The Story of a Licensed Teacher in a Paraprofessional Music Position—A Cautionary Tale. (December 2014) - Conway, Colleen; Rawlings, Jared; Wolfgram, T.J.
A trained music educator accepted a band paraprofessional position and discovered some of the challenges inherent in the role. Certified for K–12 music, he was hired part-time in a large suburban instrumental music program. The job, although interesting and challenging, did not pay enough to sustain him financially. Other music educators warned him about being "used" by the administration, but he learned a great deal from the experience and is now a full-time assistant band director. The data shared here also include statistics about increased numbers of paraprofessionals in the education field and offer a personal look at paraprofessional work.